2022
DOI: 10.3389/fimmu.2022.937476
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D metabolism pathway polymorphisms are associated with efficacy and safety in patients under anti-PD-1 inhibitor therapy

Abstract: AimVitamin D (VitD) signaling has been increasingly investigated for its role in stimulating the innate and adaptive immune systems and suppressing inflammatory responses. Therefore, we examined the associations between VitD-related genetic polymorphisms, plasma 25-hydroxyvitamin D (25(OH)D), and the efficacy and safety of immune checkpoint inhibitors (ICIs).Patients and methodsA total of 13 single-nucleotide polymorphisms (SNPs) in VitD metabolic pathway genes were genotyped in 343 cancer patients receiving I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 41 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…However, the 25(OH)D level of non-PR patients was only 16.28±5.99 ng/mL, that is, VitD insufficient, suggesting that sufficient VitD is associated with improved efficacy. A recent study also indicated that patients with higher plasma 25(OH)D levels had a better treatment response, though there was only a limited number of ICI responders in that study 22. Another study also implicated that even an increase in 25(OH)D of only 1 ng/mL was associated with an up to 3.9% reduced risk for tumor progression 23.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, the 25(OH)D level of non-PR patients was only 16.28±5.99 ng/mL, that is, VitD insufficient, suggesting that sufficient VitD is associated with improved efficacy. A recent study also indicated that patients with higher plasma 25(OH)D levels had a better treatment response, though there was only a limited number of ICI responders in that study 22. Another study also implicated that even an increase in 25(OH)D of only 1 ng/mL was associated with an up to 3.9% reduced risk for tumor progression 23.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study also indicated that patients with higher plasma 25(OH)D levels had a better treatment response, though there was only a limited number of ICI responders in that study. 22 Another study also implicated that even an increase in 25(OH)D of only 1 ng/mL was associated with an up to 3.9% reduced risk for tumor progression. 23 This difference was more pronounced in the irAE subgroup.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of all such studies, it becomes evident that additional factors are involved in bringing about the supportive role of Vitamin D to innate anti-microbial immune response. Further studies with sufficient sample size are required in this purview, which might include the role of other nutrients in complementing Vitamin D in preventing TB relapse, as well as the role of genetic polymorphisms in genes involved in the Vitamin D metabolism and Vitamin D Receptor polymorphism in bringing about a differential therapeutic effect in such subjects [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%